Keragaman Mutu Pati Beberapa Varietas Jagung - Suarni, Suarni; Firmansyah, I. U.; Aqil, M. (Jurnal Penelitian Pertanian Tanaman Pangan, 2013)
Corn-based industry requires information on physicochemical properties and functional characteristics of starch. The Information is useful as an indication of each corn variety for its usage. Corn starch characterization was done in the ICERI Laboratory of Food Processing and Chemistry Service, Maros, South Sulawesi. The starch was extracted using the wet method, and then the resulting starch was analyzed for its proximate composition, physicochemical and functional properties. The results showed that the characteristics of starch from all varieties, including moisture, ash, starch, and degree whiteness satisfied the SII (Indonesian Industrial Standard). From the eleven samples that were evaluated could be classified into three criteria, namely: low amylose content 3.98-6.87% (waxy), moderate amylose content 23.26-24.85% (Local Takalar, Anoman), slightly high amylose content 30.60-31.85% (Srikandi Putih, Srikandi kuning) and high amylose content 45.87-48.29% (Palakka, Krisna, Bisma, Lamuru). Starch components of amylose correlated with functional property and amylograf property, while the protein and fat each did not show meaningful correlation. The information obtained from this research is useful as a database of corn starch characteristic which is useful for the future corn processing and also as reference for further research.